Thus was born the SER. From oblivion by decree of Unión Radio to cohabitation with the victors of the Civil War - Afuera, Ángeles (Historia y Comunicación Social, 2021)
On March 28, 1939, Franco’s troops entered Madrid and proclaimed the end of the Civil War. The stations of Unión Radio, the first Spanish radio station, had been seized and used by the two contending fronts. Now was the time for the mercantile company to regain its ownership and resume its radio projects. Until this was achieved, he had to give the winners half of this Board of Directors, his facilities ad his own antenna, and renounce his name, known and appreciated by Spanish listeners.